Effect of Dried Whole Eggs Processed by Various Ways on Pullet's Performance and Egg Production and Quality Traits - El-Deek, A.A.; Al-Harthi, M.A. (International Journal of Poultry Science, 2009)
The effect of feeding different dietary levels of Dried Whole Eggs (DWE) processed by various ways during 14-20 wk of age on the performance of pullets up to 25 wk of age was investigated. Eggs that are not approved for human consumption were collected and then were dried at 55oC. DWE were processed by freezing at -18oC, freezing with boiling and autoclaving at 121oC. It was included in the pullet diets at 2.5 and 5%. There was also, a control diet that was fed without DWE. Thus, the experimental design was factorial (2 x 3) with added a control group (0% DWE). Each diet was fed to three replicates of 8 pullets each. Pullet's performance, egg production and quality traits and absolute and relative weight of reproductive organs was studied. Growth of pullets up to 25 wk of age was not significantly affected by various processing techniques, however, age at 50% production significantly decreased due to autoclaving compared with freezing with boiling technique. Level of 5% DWE increased growth of pullets up to 20 wk of age and this effect diminished at 25 wk of age. Laying rate, egg weight, egg mass and Feed Conversion Ratio (FCR) were significantly improved due to feeding DWE processed by freezing with boiling compared to the other methods and this was obvious within each DWE level. Age at 50% production significantly decreased and egg production traits significantly improved due to inclusion of 5% DWE. Egg quality traits of fresh eggs were not significantly affected by DWE level and/or technique of processing. However, freezing technique maintained better Haugh unit score and freezing with boiling maintained better yolk index after stored for one month in the refrigeration. On the other hand, 2.5% DWE maintained shell thickness and Haugh unit score of eggs stored for one month in the refrigeration. Absolute and relative weight of organs were significantly affected by processing methods and/or DWE levels and 5% DWE significantly increased absolute and relative weight of blood, intestinal length and leg color while significantly decreased absolute and relative weight of liver and absolute weight of intestinal. In conclusion, up to 5% frozen with boiled DWE can be included in the pullet's diets during 14-20 wk of age without adverse effect on pullet's performance and egg production and quality traits up to 25 wk of age.